INVESTIGATING THE NUCLEAR ACTIVITY OF BARRED SPIRAL GALAXIES: THE CASE OF NGC 1672 - Jenkins, L. P.; Brandt, W. N.; Colbert, E. J. M.; Koribalski, B.; Kuntz, K. D.; Levan, A. J.; Ojha, R.; Roberts, T. P.; Ward, M. J.; Zezas, A. (IOP, 2011)
We have performed an X-ray study of the nearby barred spiral galaxy NGC 1672, primarily to ascertain the effect of the bar on its nuclear activity. We use both Chandra and XMM-Newton observations to investigate its X-ray properties, together with supporting high-resolution optical imaging data from the Hubble Space Telescope (HST), infrared imaging from the Spitzer Space Telescope, and Australia Telescope Compact Array ground-based radio data. We detect 28 X-ray sources within the D₂₅ area of the galaxy; many are spatially correlated with star formation in the bar and spiral arms, and two are identified as background galaxies in the HST images. Nine of the X-ray sources are ultraluminous X-ray sources, with the three brightest (LX > 5 × 10³⁹ erg s⁻¹) located at the ends of the bar. With the spatial resolution of Chandra, we are able to show for the first time that NGC 1672 possesses a hard (Γ ~ 1.5) nuclear X-ray source with a 2-10 keV luminosity of 4 × 10³⁸ erg s⁻¹. This is surrounded by an X-ray-bright circumnuclear star-forming ring, comprised of point sources and hot gas, which dominates the 2-10 keV emission in the central region of the galaxy. The spatially resolved multiwavelength photometry indicates that the nuclear source is a low-luminosity active galactic nucleus (LLAGN), but with star formation activity close to the central black hole. A high-resolution multiwavelength survey is required to fully assess the impact of both large-scale bars and smaller-scale phenomena such as nuclear bars, rings, and nuclear spirals on the fueling of LLAGN.